PELAYANAN GEREJA DALAM PENDAMPINGAN PASTORAL TERHADAP JEMAAT YANG MENGHADAPI TEKANAN EKONOMI DI GMIT SALEM PASI - Selfina Tande; Agnes Magdelina Kolly; Adolfina Oualeng (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Economic pressure is one of the major challenges experienced by many church members, especially in communities that rely heavily on agriculture as their primary source of livelihood. Members of GMIT Salem Pasi frequently encounter economic difficulties caused by crop failure, unpredictable weather conditions, pest attacks, and unstable household income. These conditions affect not only their economic well-being but also their social, emotional, and spiritual lives. In such circumstances, the church has a pastoral responsibility to provide assistance that addresses the needs of congregation members holistically. This study aims to describe the church's pastoral ministry for congregation members experiencing economic pressure at GMIT Salem Pasi, identify the obstacles encountered in its implementation, and examine the changes experienced by congregation members after receiving pastoral assistance. The study employed a qualitative descriptive approach. Data were collected through in-depth interviews with the pastor, deacons, and congregation members facing economic difficulties. Data analysis followed the interactive model of Miles and Huberman, consisting of data reduction, data presentation, and conclusion drawing. The findings reveal that pastoral assistance was implemented through pastoral visits, household worship services, pastoral oikos ministry, prayer meetings, pastoral counseling, diaconal services, and economic empowerment programs such as skills training and integrated farming. These ministries contributed positively to the congregation by strengthening faith, providing emotional comfort, increasing hope, and motivating members to persevere amid economic hardship. However, the church also faced several challenges, including limited financial resources, insufficient church personnel, geographical barriers, and the reluctance of some congregation members to openly discuss their economic struggles. The study concludes that holistic pastoral ministry plays a significant role in helping congregation members cope with economic pressure while strengthening their spiritual resilience and overall well-being.